An electromagnetic field disrupts negative geotaxis in Drosophila via a CRY-dependent pathway - Fedele, Giorgio (Nature Pub. Group, 2014)
Many higher animals have evolved the ability to use the Earth’s magnetic field, particularly for orientation. Drosophila melanogaster also respond to electromagnetic fields (EMFs), although the reported effects are quite modest. Here we report that negative geotaxis in flies, scored as climbing, is disrupted by a static EMF, and this is mediated by cryptochrome (CRY), the blue-light circadian photoreceptor. CRYs may sense EMFs via formation of radical pairs of electrons requiring photoactivation of flavin adenine dinucleotide (FAD) bound near a triad of Trp residues, but mutation of the terminal Trp in the triad maintains EMF responsiveness in climbing. In contrast, deletion of the CRY C terminus disrupts EMF responses, indicating that it plays an important signalling role. CRY expression in a subset of clock neurons, or the photoreceptors, or the antennae, is sufficient to mediate negative geotaxis and EMF sensitivity. Climbing therefore provides a robust and reliable phenotype for studying EMF responses in Drosophila.